The Comparison of X-ray Finding in Pulmonary Tuberculosis with and without Diabetes Mellitus - Ida Bagus Aditya Nugraha; Wira Gotera; Made Nian Anggara (PP PERKENI, 2024)
Diabetes Mellitus patients are considered as a high-risk population for the development of Pulmonary Tuberculosis (PTB) by about three-fold. Diabetes Mellitus sufferers by glycated haemoglobin A1C (HbA1C) level. The relative risk (RR) of Tuberculosis (TB) was 3,1 (95% CI 1.6-5.9) for those with HbA1C ≥7%. There are several contradictory opinions regarding the radiological appearance of TBC sufferers with genuine effect of DM. Chest X-ray remains the primary investigation for the assessment of PTB. Pulmonary Tuberculosis is found predominantly in the lung apices. It is not clear whether DM can affect the presentation of TB. Thus, whether diabetic subjects present atypical radiological presentation of PTB is still controversial. There have been several studies with contradictory results regarding the differences in the radiological appearance of PTB patients with and without DM. Clinical studies have shown ambiguous results. Any other risk factors maybe associated with age, sex, smoking status, and nutrition status.